Applied Ore Microscopy in Solving Concentration Problems of Pb-Zn-Ag Ore Rich with Sb and As - R. Tomanec; M. Blagojev (International Mineral Processing Congress, 2018)
"Studies reported in this paper used polymetallic Pb-Zn-Sb-As-(Ag, Au) ore from Dražnja, Kosovo. The ore is comparatively rich in Zn (6.56%) and Pb (2.87%), but with high rates of Sb and As. Conventional lead and zinc concentration by flotation produced galena and sphalerite rich concentrate with high recovery, but with excessive As and Sb. After chemical analyses, which could not detect the reason for the excessive elements, ore minerals were identified under the ore microscope, their texture characterized, and degree of liberation of useful minerals was assessed. Microscopy of the mineral concentrates revealed complex intergrowths of galena and marmatite minerals mostly with sulphosalt minerals (boulangerite, jamesonite and bournonite) and also with arsenopyrite mainly responsible for the unsatisfactory quality of the concentrate. These complex sulphosalts, among other things have similar behaviour during the flotation concentration, and in spite of their interlocking with galena, therefore inadequate liberation, sulphosalts remain in the lead concentrate. Microscopic analyses indicated that a better galena concentration product is possible with a higher rate of mineral liberation, and then by selective floc flotation of some sulphosalt minerals. Purpose of this work was to show that only chemical analysis is not sufficient, according to that we solved the problem by precise mineral identification and time consuming mineral liberation measurements. INTRODUCTION The polymetallic Pb-Zn-Sb-As-(Ag, Au) ore body of Dražnja, Kosovo, fairly rich in Zn (6.56%) and Pb (2.87%) was repeatedly explored and once even worked. Mineralization at Draznja was primarily represented by sphalerite, galenite and marcasite/pirite. Some sections comprise massive sulphides, and others are lower grade zones of semi-massive sphalerite/galena or marcasite/pyrite dominant sulphides. The ore body II was formed in the southern gallery in the structure Çukë – Lajthishtë (with content of 3.16% Pb and 7.31% Zn). Pb-Zn ore with increased content of As, Sb sulphosalts is not rare phenomenon in the world. While previously treated as unprofitable, economical uninteresting ore, today with development processing and new reagents (organic, ecologic), are the topic of scientific papers. The examination of Pb-Zn ore with high content of sulphosalts we find in deposits as: The hydrothermal vein deposit of Harja in the Baia Mare area, contain a wide variety of sulphosalts [Cook, N. & Damian, G., 1997]; also the deposits Fankou Mine in Guangdong Province and the Dachang Mine in Guangxi Province, where the flotation concentration of galena and jamesonite takes place [Runqing Liu et al. 2015], [Zhang Ting, Qin Wen-Qing, 2015];. On a samples from Tibet in China flotation separation test of galena and jamesonite was conducted [Sun Wei, Han Haisheng, Tao Hongbiao, Liu Runqing, 2015]. According to history of investigation, the mineralized area of Dražnja has a long history of exploration and possible exploitation activities [Slowey, Galen, 2009]. Recent workings were carried out in three stages through the 20th century."